EVALUASI TITIK KONTROL TINGGI UNIVERSITAS NEGERI SEMARANG DENGAN METODE PENGUKURAN KERANGKA DASAR VERTIKAL BENCH MARK (BM) - Safrel, Ispen (Semarang State University, 2010)
Abstract: In 2009, State University of Semarang (UNNES) had engaged in the measurement of the FrameworkÃ‚Â forÃ‚Â theÃ‚Â HorizontalÃ‚Â andÃ‚Â VerticalÃ‚Â BasicÃ‚Â FrameworkÃ‚Â usingÃ‚Â GlobalÃ‚Â PositioningÃ‚Â Systems (GPS)Ã‚Â geodeticÃ‚Â typeÃ‚Â andÃ‚Â installationÃ‚Â ofÃ‚Â twoÃ‚Â benchÃ‚Â markÃ‚Â (BM),Ã‚Â howeverÃ‚Â theÃ‚Â heightÃ‚Â ofÃ‚Â its developmentÃ‚Â (Z)Ã‚Â in aÃ‚Â region onÃ‚Â the surface ofÃ‚Â the earth always changing and growing discourse according to some, especially for the city of Semarang itself reportedly decreased Ã‚Â± 5 cm from the average seaÃ‚Â level (MSL) each year. What aboutÃ‚Â the height of Campus UNNES have now?,Ã‚Â InÃ‚Â this study need to be investigated how much elevation change from a position (Unnes campus) in 2010. Measurement of vertical control framework BM Unnes tied to the High Point Geodesy (TTG) with a height of 221 004 449 number MSL in the area